Effect of expiration date of universal adhesives on the alterations of microtensile bond strength of composite resin to dentin - Golara Azarpira; Ghazaleh Ahmadizenouz; Faraneh Mokhtarpour; Fariba Ezoji (Babol University of Medical Sciences, 2022)
Introduction: One of the factors affecting the success of bonded restoration is the use of appropriate adhesives and attention to their maintenance time. The aim of this study was to investigate the effect of three time periods related to the expiration date of two universal adhesives on the bond strength of resin composite to dentin. Materials & Methods: In this in-vitro study, 30 intact third human molars were selected. The roots of the teeth were cut and the crown part was mounted in acrylic resin in such a way that the enamel of the buccal surface was clearly visible. Using abrasive disks, the enamel of the buccal surface of the teeth was abraded to create a flat dentin area with dimensions of 25 mm2. The samples were randomly divided into 2 groups based on adhesive type (All Bond (Bisco, Fchaumburg,IL, USA) G-Permio  and each group was divided into 3 subgroups based on expiration date. After the bonding process and fabrication of composite samples, microtensile bond strength (TBS) was measured at a speed of 1 mm/min. The data were analyzed using the Kruskal-Wallis test and post hoc Tukey's test. P<0.05 was considered as significant level. Results: Significant differences were found among samples with different expiration dates in both All-Bond Universal (p=0.0001) and G-Premio (p=0.0001) groups in terms of micro TBS (μTBS). In both adhesive groups, a significant difference was found between 2 months after expiration with expiration time and 2 months before expiration, but there was no significant difference between expiration time and 2 months before expiration. Conclusion: The end of the expiration date has a reducing effect on the μTBS of universal adhesives investigated in this study. However, the amount of this effect varies depending on the type of adhesive.